2018
DOI: 10.1002/micr.30368
|View full text |Cite
|
Sign up to set email alerts
|

Wrist arthrodesis with the medial femoral condyle flap: Outcomes of vascularized bone grafting for osteomyelitis

Abstract: These cases illustrate the use of the MFC in wrist arthrodesis after osteomyelitis defects. In all cases, there was complete union in a short time, no recurrence of infection, and low donor-site morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…It is well-known that the osteogenic potential of a vascularized graft allows more reliable and rapid fusion than cancellous bone graft or allograft. 17 Moreover, according to Mattos et al, 12 besides the structural and osteogenic advantages that VBG offer, one chief advantage is the delivery of systemic antibiotics to the infected radiocarpal area and hastened bone integration. There are risks of performing vascularized allograft, due to donor-host immunity, and necessity of continued immunosuppressive drugs, even with the availability of more advanced drugs; therefore, currently there is no indication for such grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that the osteogenic potential of a vascularized graft allows more reliable and rapid fusion than cancellous bone graft or allograft. 17 Moreover, according to Mattos et al, 12 besides the structural and osteogenic advantages that VBG offer, one chief advantage is the delivery of systemic antibiotics to the infected radiocarpal area and hastened bone integration. There are risks of performing vascularized allograft, due to donor-host immunity, and necessity of continued immunosuppressive drugs, even with the availability of more advanced drugs; therefore, currently there is no indication for such grafts.…”
Section: Discussionmentioning
confidence: 99%
“…This will represent a serious clinical challenge, but one that must be taken seriously, since delay in treatment will be devastating for the anatomic structures and could increase the risk of amputation. [12][13][14] As the infection progresses, an intense inflammatory response will evolve, leading to the production of microthrombi, depleting circulation, decreasing oxygen perfusion, and ultimately causing necrosis and lysis of the bone, with structure collapse. 14 At this stage, the infection is notoriously difficult to treat.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 It has been employed to perform wrist arthrodesis, repair scaphoid fracture non-unions, and distal radial metaphyseal nonunions. 3,5 The MFC flap has been used to reconstruct the nose after rhinectomy, to repair partial or total maxillectomy defects, and repair the premaxilla in a patient with median facial dysplasia. [6][7][8] Gaggl et al have successfully used an osteoperiosteal femur flap to treat defects of the anterior maxillary alveolar ridge after tooth loss in 5 patients with clefts of lip, palate, and alveolus.…”
Section: Discussionmentioning
confidence: 99%
“…2 This flap has most commonly been used for bony defects or non-unions of the extremities after trauma or tumor resection, including thumb fractures, wrist osteomyelitis, and distal radius and femur non-union. [2][3][4][5] The MFC flap has also been used to reconstruct craniofacial osseous defects in the nasal bones, maxilla, and mandible. [6][7][8] An alveolar cleft (AC) defect must be repaired to support eruption of the cleft-side lateral incisor and canine, closure of oronasal fistulae, and creation of a continuous maxillary arch.…”
Section: Introductionmentioning
confidence: 99%
“…4 Also free osseous flaps such as a medial femoral condylar flap and a vascularized fibula can be used for successful healing. 10 Recent studies have demonstrated that performing a TWF results in a high degree of patient satisfaction with mean Disabilities of the Arm, Shoulder and Hand (DASH) scores of 25 to 38. [11][12][13][14][15] However, Wei and Feldon reported an overall complication rate of 29% among 1,782 wrist arthrodeses, and a reoperation rate of 19%.…”
mentioning
confidence: 99%